18F-Fluoride PET/CT Imaging of Medication-Related Osteonecrosis of the Jaw in Conservative Treatment—A Case Report - Reinert, Christian Philipp; Pfannenberg, Christina; Gatidis, Sergios; la Fougère, Christian; Nikolaou, Konstantin; Hoefert, Sebastian (Frontiers in Oncology, 2021)
Medication-related osteonecrosis of the jaw (MRONJ) is a serious side effect in antiresorptive treatment. Treatment of MRONJ is considered primarily conservative with oral mouth rinses and antibiotics but may demand surgery, depending on the complaints and general condition of the patient, the extent of the necrosis, and the overall prognosis with respect to the underlying disease. A 77 year old female patient with invasive ductal breast cancer and bone metastases was treated with intravenous bisphosphonate (BP) zoledronic acid. During therapy, she developed MRONJ in the mandible with severe pain. Clinical examination revealed confluent exposed bone of the lower left jaw and a fistula at the right molar region. The panoramic radiograph revealed a mandibular osseous involvement with diffuse radiopaque areas between radiolucent areas. For preoperative planning, 18F-fluoride positron emission tomography/computed tomography (PET/CT) of the jaw was performed, showing substantially increased 18F-fluoride uptake in regions 38 to 47 of the mandible with a focal gap in region 36 (area of clinically exposed bone). CT revealed medullary sclerosis and cortical thickening with confluent periosteal reaction and focal cortical erosion in the regions 37 to 42, whereas the regions 43 to 47 were only subtly sclerotic without cortical thickening. After systemic antibiotic therapy with sultamicillin following significant symptom and pain relief, 18F-fluoride PET/CT imaging was performed again after 5 months. No changes in either CT and PET were observed in regions 38 to 42, whereas the bony sclerosis was slightly increased in regions 43 to 47 with a slight reduction of 18F-fluoride uptake. 18F-fluoride PET/CT showed no significant changes assessing the extent of MRONJ prior and after systemic antibiotic therapy, providing no evidence that conservative treatment reduced the extent of the MRONJ-affected jawbone. The additional information of 18F-fluoride PET enables to identify the true extent of MRONJ which may be underestimated by CT imaging alone. Patients with MRONJ undergoing conservative treatment could benefit because additional imaging may be avoided as the pre-therapeutic 18F-fluoride PET/CT delivers all information needed for further treatment. Our findings support the recommendation of a surgical approach as long-term antibiotics cannot downsize the extent of MRONJ.